Conditions and Factors Influencing Corporate Ecologic Responsibility at Steel-Making Enterprises in Russia - I. A. Kostylev (Вестник Российского экономического университета имени Г. В. Плеханова)
The article analyses conditions and factors, which affect realization of corporate ecologic responsibility at steelmaking enterprises in Russia. Special attention is paid to motivation of companies to keep to responsible work and assess its compliance with set standards. The research covers motivation of steel-making enterprises in respect of practices aimed at improving the ecologic situation, both internal and external factors are studied. The article analyzed current practices of big steel-making companies of Russia. The author investigates a wide range of factors that can influence company decisions in the field of ecologic responsibility. As a result the article provides a complete picture of the current situation and prospects of developing corporate ecologic responsibility at steelmaking enterprises in Russia.